The influence of servant leadership on trust, psychological empowerment, job satisfaction and organisational citizenship behaviour on a selected sample of teachers in the Western Cape Province - Van Der Hoven, Adrian Geoffrey (University of the Western Cape, 2017)
Magister Commercii (Industrial Psychology) - MCom(IPS) === School principals and teachers play a vital role of imparting the important skills required for successful learning performance and further education and training (Mahembe & Engelbrecht, 2013). Teachers are responsible for the production of quality primary and secondary school graduates who will constitute the future human capital base for the country to be able to achieve its competitive advantage. The role of the principal as a servant leader is vital to an academic institution such a school. A principal that adopts a servant leadership approach enables teachers and the School Management Team (SMT) to function as a collective and potentially improve or create an environment conducive for governance, teaching and learning. Therefore, effective leadership is essential to develop good schools with teachers that trust their leader, are satisfied in their jobs, feel empowered and will go beyond the call of duty. A principal as a servant leader, including a departmental head, can shape the school working environment to provide greater opportunities for exhibiting positive behaviors and outcomes that are likely to promote job satisfaction and organisational citizenship behaviour (OCB). The purpose of the current research study is to answer the question, "What is the influence of servant leadership on trust, psychological empowerment, job satisfaction and OCB amongst teachers at selected schools in the Western Cape Province?" In order to answer the research question explaining the hypothesised relationships, the research study developed a theoretical model and tested an explanatory structural model to explain the manner in which servant leadership influences trust, psychological empowerment, job satisfaction and organisational citizenship behaviour. The study was conducted using teachers drawn from selected schools in the Western Cape Province of South Africa. The participants were asked to complete five self-reporting questionnaires comprising the Servant Leadership Questionnaire (SLQ), the Leadership Trust Scale (LTS), Measuring Empowerment Questionnaire (MEQ), Job Satisfaction Scale (JSS), and the Organisational Citizenship Behaviour Scale (OCBS). A total of 203 (n=203) questionnaires were returned out of a distributed total of 330 questionnaires. Item and dimensionality analyses were conducted on all of the dimensions using SPSS version 23. Subsequently, confirmatory factor analysis (CFA) was executed on the measurement models of the instruments used. The proposed conceptual model was evaluated using structural equation modelling (SEM) via the LISREL version 8.80 software. It was found that both the measurement and structural models fitted the data reasonably well. The results indicated a significant and positive relationship between servant leadership and trust; servant leadership and psychological empowerment; servant leadership and job satisfaction; psychological empowerment and trust; psychological empowerment and job satisfaction; and psychological empowerment and OCB. However, there is a non-significant relationship between servant leadership and OCB. Furthermore, the relationship between job satisfaction and OCB is negative and insignificant. This study will add significance to the body of knowledge by attempting to give insight as to whether servant leadership influences teachers towards engaging in extra role behaviours. The practical implications of the study and limitations are discussed as well as the direction for future research studies.